The effect of BMP-2, BMP-4 and BMP-6 on bone destruction of cholesteatoma presence - Oger, Muzaffer; Alpay, Hayrettin Cengiz; Orhan, Israfil; Onalan, Ebru Ethem; Yanilmaz, Muhammed; Sapmaz, Emrah (W B Saunders Co-Elsevier Inc, 2013)
Objective: The aim of our study was to investigate the relationship between the destruction of temporal bone structures, ossicular chain destruction, dissemination of cholesteatoma and the expressions of bone morphogenetic proteins (BMPs), BMP-2, BMP-4 and BMP-6 in patients with acquired cholesteatoma. Material and Methods: This study was performed in a total of 80 patients with cholesteatoma and without cholesteatoma who had undergone surgery due to chronic otitis media. The patients were grouped as the study and the control groups. The study group comprised patients with primary acquired cholesteatoma, and the control group consisted of chronic otitis media patients without cholesteatoma. The samples were obtained from cholesteatoma tissue and the external acoustic meatus skin in study group patients and they were obtained from the external acoustic meatus skin only in control group patients. The Reverse Transcriptase Polymerase Chain Reaction method was used for the measurements of BMPs, BMP-2, BMP-4 and BMP-6 expressions. Polymerase Chain Reaction was studied by isolation of Ribonucleic Acid from the tissue samples. Results: When the expressions of BMP in the external acoustic meatus skin were compared between the study and the control groups, the BMPs, BMP-2 and BMP-6 were determined to have a statistically significant relation in the study group (p < 0.05), but BMP-4 was not significant (p > 0.05). When the expression of BMP in cholesteatoma tissue was investigated in the study group patients, the BMPs, BMP-2 and BMP-6 were determined with statistically significant positivity (p < 0.05), but there was no significant positivity for BMP-4 (p > 0.05). In the study group, there was no statistical significance between the expressions of BMPs, BMP-2, BMP-4 and BMP-6 in cholesteatoma tissue, in the external acoustic meatus skin, and temporal and ossicular chain destruction, and dissemination of cholesteatoma (p > 0.05). A statistically significant positivity for BMPs expression in cholesteatoma tissue was determined in patients with destruction of the incus + malleus + stapes (p < 0.05). Conclusion: The expressions of BMPs, BMP-2 and BMP-6, were elevated in cholesteatoma tissue. Furthermore, the positivity of BMPs expression was statistically significant in patients with destruction of all the ossicles, and we think that this marker can be used for evaluation of the aggressiveness of cholesteatoma. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Necrosis-Factor-Alpha; Chronic Otitis-Media; Expression; Interleukin-1-Alpha